Islamic Entrepreneurship Based On Maqashid Sharia in Increasing Competitive Advantage MSMES in Sinjai - Permata, Srianti; Hadijah Wahid, St. (FITRAH: Jurnal Kajian Ilmu-ilmu Keislaman, 2024)
The significant growth of MSMEs in Sinjai Regency, run mainly by the Muslim community, indicates the need to implement a new orientation in MSMEs to maintain a balance between economic activities and Islamic Sharia principles. This study examines how Islamic entrepreneurship based on maqashid sharia increases the competitive advantage of MSMEs in Sinjai Regency. This qualitative research produces descriptive data through words written or spoken by individuals and observed behaviours. This approach involves an in-depth exploration of literature, data, and numbers so that it can understand reality thoroughly. Based on the results of the research that has been carried out on Islamic entrepreneurship in developing Competitive Advantage with observation, interview and documentation methods, researchers conclude that empirical evidence has been found from as many as six resource persons about Islamic Entrepreneurship in Sinjai Regency, especially in halal labelling, there are still many MSME actors who do not know and have difficulties in applying the halal labelling process, and in the application of Islamic principles entrepreneurship in developing competitive advantage has been found five speakers who stated the same thing that MSME actors had applied the principles of Islamic Entrepreneurs in this trade, as evidenced by the ways carried out by MSME actors that remain valid, namely honesty, trust, and alms and are responsible for their mandatory worship and sunnah worship.